KETERAMPILAN MANAJERIAL KEPALA SEKOLAH PEREMPUAN: STUDI KASUS KEPALA SEKOLAH MENENGAH ATAS NEGERI 6 KOTA CIREBON - Asep Kurniawan (IAIN Syekh Nurjati Cirebon, 2019)
So far, women's leadership is still underestimated; especially her managerial skills as a principal in an educational institution.Actually, she can lead the school and bring it to good quality. This research was intended to further uncover the conceptual skills, human skills and technical skills of female principals in State High Schools 6 Cirebon City. This research was a survey research. The respondents were 250 students. The research instrument was a questionnaire. The result showed that the principal’s managerial skills of State High Schools 6 Cirebon City were very good. It could be viewed from the conceptual skills (86.4%) and human skills (83.2%) were very good. Meanwhile, technical skills were good (76.8%). Based on the results of the respondents' assessment, the technical skills of female principals of State High Schools 6 Cirebon City were lower than conceptual and human skills.Keywords: ability, gender, assessment